Integrated management of rodents in cauliflower (Brassica oleracea var botrytis subvar cauliflora) in Himachal Pradesh - SHEIKHER, CHANDER; SOOD, PANKAJ (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1996-99 to formulate integrated management of the rodent pests inhabiting cauliflower (Brassica oleracea L. var botrytis L. subvar cauliflora DC.) fields of mid-hills of Solan (Himachal Pradesh). Bandicota begalensis (Gray), Rattus meltada (Gray), R. rattus (Gray), Mus booduga (Gray) and M. platyhrix were the inhabitant any rodent species in caulifloweer fields. They inflicted 6.78% damage in curd crop and 8.43% in seed crop in absence of any rodent-management practices. In curd crop this damage was deduces to 3.2% when chemical control was employed symtomatically (4 treatments as and when rodent activity was recorded in the fields) thereby saving a loss of 908 kg edible curd/ha, and to 2.05% when integrated management was undertaken, with a saving loss of 1 205 kg/ha. In seed crop, the symptomatic control reduced the rodent loss to 4.43% and integrated management to 2.86%. The saving in terms of seed yield was 15.18 and 23.81 kg/ha respectively with these 2 management programmes. The net gain (after compensating the expenditure incurred on control programme) was Rs 3 427 and Rs 4 453/ha with sysptomatic and integrated management respectively in curd crop and Rs 7 700 and Rs 11 523/ha respectively in seed crop.